ON THE ISSUES OF THE DEVELOPMENT OF SOME ASPECTS OF THE MODERN INNOVATION SYSTEM - Mirzakarimov Javlonbek; Uzganbayeva Dilnoza Toxtasinovna (European Science Publishing, 2024)
The article is devoted to the formation and development of the national innovation system of the Republic of Uzbekistan. The article examines and describes the reasons and factors influencing the formation and development of the national innovation system, problems and ways to solve them, as well as the model of the national innovation system.
Keywords: innovation, innovation economy, innovation model, national innovation system, innovation activity, technological progress, effective management.